Multi-Users Dynamic Bandwidth Allocation Technology of SDTN - Jianxiang CHU; Yin HUANG; Chong WANG; Yunze CAO (天地一体化信息网络)
The TT＆amp;C and data transmission of spacecraft are divided into two methods: space-based and ground-based.Among them, space-based method has the advantages of global coverage, access at any time, and real-time information return, and have a wide range of application prospects.But it also puts forward certain requirements for the dynamic bandwidth allocation of its multi-spacecraft.Based on the studied of medium-orbit TT＆amp;C, data transmission constellation network architecture and multiple access protocols, a dynamic bandwidth allocation algorithm for on-doard multi-beam, multi-spacecraft users, and multi-task priorities for data transmission tasks was proposed.It was very suitable for the on-demand and real-time resource allocation of data transmission requests of multiple spacecraft in the mid-orbit constellation, and could be used as a multiple access protocol model for space-based measurement and control and data transmission access networks.